HOSOYA POLYNOMIAL OF A MULTI-BRIDGE GRAPH - Ncambalala, T; Mphako-Banda, E.G (TWMS journal of applied and engineering mathematics, 2021)
Explicit expressions of the Hosoya polynomials of some classes of graphs are known. In this paper we find an explicit expression for the Hosoya polynomial of the multibridge graph. Finally we give some examples of multi-bridge graphs which are chemical graphs. Keywords: Hosoya polynomial, Wiener index, uniform multi-bridge graph, graph distance, inclusion-exclusion principle. AMS Subject Classification: 05C31, 92E10, 05C12.